Effect of lindane on protein nutritive utilization in trout (Salmo gairdneri) (Revista Española de Fisiología, 1981)
Rainbow trout weighing 100 + 10 g were fed three diets of different proteic content (67.6%, 53.2% and 36.1%) and exposed to 0.01 and 0.001 ppm of Lindane in water during 21 days.The parameters calculated were: Protein Productive Value (PPV), Conversion Index (CI) and Protein Efficiency Ratio (PER).The PPV parameter increased with a diet proteic level decrease, at control and at Lindane treated groups.Minimum protein utilization corresponds to 67.6% proteic content diet and 0.01 ppm Lindane, while maximum, to 36.1% proteic content and Lindane 0.001 ppm.The CI and PER parameters were markedly different in groups on extreme diets (67.6% and 36.1%) with higher contamination level (0.01 ppm) from all the others.The experimental parameters were not practically affected by the presence or absence of Lindane in groups on diets of medium proteic content.